2008
DOI: 10.1111/j.1442-200x.2008.02642.x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous closure of perimembranous ventricular septal defect after school age

Abstract: SC occurred in 23% of patients with a P-VSD of Qp/Qs < 1.7 up to adolescence. But a P-VSD of Qp/Qs >or= 1.2 showed no tendency to close spontaneously. The factor most influencing SC of P-VSD after school age seemed to be the shunt ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…Muscular VSDs tend to close in 80% cases early in life,21 22 25 32–36 a frequency that is at least twice the frequency of spontaneous closure for perimembranous VSDs 25. Spontaneous closure may occur up to age 6 years25 or beyond school age for perimembranous VSDs 23. Interestingly, the presence of partially occluding accessory tissue is not predictive of spontaneous closure 23…”
Section: Resultsmentioning
confidence: 99%
“…Muscular VSDs tend to close in 80% cases early in life,21 22 25 32–36 a frequency that is at least twice the frequency of spontaneous closure for perimembranous VSDs 25. Spontaneous closure may occur up to age 6 years25 or beyond school age for perimembranous VSDs 23. Interestingly, the presence of partially occluding accessory tissue is not predictive of spontaneous closure 23…”
Section: Resultsmentioning
confidence: 99%
“…In most cases, the constructive tissue of AMS is usually derived from the tricuspid valve but not from the septal membrane itself (17). In spite of the association between VSD and AMS, Miyake et al suggested that there was no relation between the closure and AMS because AMS was detected in 48% (23 of 48) of patients with perimembranous VSD, and of the 23 defects with AMS, only 4 (17%) closed spontaneously (30). Some authors believe that perimembranous VSD is closed by tricuspid pouch.…”
Section: Mechanisms Responsible For Spontaneous Vsd Closurementioning
confidence: 99%
“…Complete or partial closure may occur by adhesion of the septal leaflet of the tricuspid valve to the edge of the defect, often with formation of an aneurysm. The prevalence of an AMS in patients with a membranous VSD is reported by the earlier-mentioned studies of Miyake et al and Neumayer et al to be as high as 48 % during childhood [3] and 10 % above 17 years of age [4].…”
Section: Discussionmentioning
confidence: 83%
“…In membranous VSDs spontaneous closure is frequent. During childhood, 23 % (0-33 %) of the small membranous VSDs close spontaneously [3] and after the age of 17, a smaller portion of 4-10 % close spontaneously [4,5]. Complete or partial closure may occur Electronic supplementary material The online version of this article…”
mentioning
confidence: 99%